2012
DOI: 10.1021/jo301134q
|View full text |Cite
|
Sign up to set email alerts
|

The Element Effect Revisited: Factors Determining Leaving Group Ability in Activated Nucleophilic Aromatic Substitution Reactions

Abstract: The “element effect” in nucleophilic aromatic substitution reactions (SNAr) is characterized by the leaving group order, F > NO2 > Cl ≈ Br > I, in activated aryl halides. Multiple causes for this result have been proposed. Experimental evidence shows that the element effect order in the reaction of piperidine with 2,4-dinitrophenyl halides in methanol is governed by the differences in enthalpies of activation. Computational studies of the reaction of piperidine and dimethylamine with the same aryl halides usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
(75 reference statements)
3
45
0
Order By: Relevance
“…For pyridine, the [M + 77] + ion yield increased in the order Cl < Br < I, which is in good agreement with earlier reports of nucleophilic substitution between halobenzene radical cations and small amines in the gas phase [42,43]. This reactivity order is reasonably explained by the oppositely directed order of C 6 H 5 -X bond strengths (I < Br < Cl < F [44]), and it is opposite to what has been reported for nucleophilic aromatic substitution involving neutral halo-, and nitrosubstituted benzenes in solution and in gas phase [45,46]. For 2-methylpyridine the highest [M + 77] + yield was observed with bromobenzene dopant.…”
Section: Appi Measurementssupporting
confidence: 89%
See 1 more Smart Citation
“…For pyridine, the [M + 77] + ion yield increased in the order Cl < Br < I, which is in good agreement with earlier reports of nucleophilic substitution between halobenzene radical cations and small amines in the gas phase [42,43]. This reactivity order is reasonably explained by the oppositely directed order of C 6 H 5 -X bond strengths (I < Br < Cl < F [44]), and it is opposite to what has been reported for nucleophilic aromatic substitution involving neutral halo-, and nitrosubstituted benzenes in solution and in gas phase [45,46]. For 2-methylpyridine the highest [M + 77] + yield was observed with bromobenzene dopant.…”
Section: Appi Measurementssupporting
confidence: 89%
“…TS1 for fluorobenzene, calculated as Δ R G Ø ‡ = 12.1 kJ/mol is significantly lower, which can be explained by strong localization of the positive charge at C 1 due to the electronegativity of fluorine (see Figure S2 in Supplementary Material). The activation energy for this reaction step increases with the size of the halogen, which can be due to sterical effects, or due to the localized positive charge at the ipso-carbon of the smaller halobenzene radical cations [46]. Additionally, heavier halogens have to move out of the phenyl ring plane.…”
Section: Appi Measurementsmentioning
confidence: 99%
“…Moreover, the leaving group ability in activated ANS was recently revised, and the authors found that the leaving group order in gas phase is or would be dependent on the exact combination of nucleophile, leaving group and substrate framework. The geometry of the ANS transition state permits useful, qualitative conceptual distinctions to be made between this type of reaction and other modes of nucleophilic attack . The authors report computational studies of the reaction of piperidine and dimethylamine with the aryl halides using methanol as solvent; the results indicate that polarizability, solvation and negative hyperconjugative effects are all relevant in producing the element effect in methanol …”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, there are abundant literature reports about ANS studies referred to elucidate the factors that influence the reactivity in ANS and its many applications in organic chemistry, biochemistry and industrial processes. To cite some of the more recent, it has been reported the arylation of heteroatom nucleophiles by using activated haloarenes, with or without metal catalysts, while experimental and computational studies have been carried out on the factors determining the leaving group ability, the preferential solvation and the reactivity indices profile as a tool for the analysis of reaction mechanisms in activated ANS. Furthermore, it is worth mentioning the importance of ANS in sustainable chemistry, including a treatment of halohydrocarbons and polychlorinated biphenyls for the decontamination of groundwater and the elimination of chlorine in the synthesis of 4‐aminodiphenylamine…”
Section: Introductionmentioning
confidence: 99%
“…So it is clear that the yields of 4a in both cases using either water or acetic acid is very tight in most instances by using microwave 11 irradiation, but the use of water as green solvent was advantaged than acetic acid. 37 This order clearly suggests that stronger bond dipoles associated with the more electronegative atom favor the addition step thus lowering the energy of activation of the nucleophilic addition step which is rate-determining step. It is worth mention that the short reaction times, easy workup, the excellent yields, and mild reaction conditions make this Knoevenagel type condensation reaction followed by cycloaddition then intramolecular exocyclic cyclization via addition -elimination mechanism (S N Ar), both practical and attractive.…”
mentioning
confidence: 99%